Mechanism of xanthine oxidase in flap ischemia-reperfusion injury and advances in targeted therapy: a mini review - Jia, Weidong; Wei, Xin; Gong, Xu (Frontiers in Physiology, 2025)
Ischemia-reperfusion injury in flaps refers to a cascade of pathophysiological reactions that aggravate tissue damage or even cause necrosis. During the period of ischemia followed by restored blood reperfusion, a burst of reactive oxygen species is produced. The prevention of flap ischemia-reperfusion injury remains a critical and challenging focus in current research. Xanthine oxidase serves as a major source of reactive oxygen species during ischemia-reperfusion. Allopurinol and febuxostat, xanthine oxidase inhibitor, primarily exerts its protective effects by inhibiting the activity of xanthine oxidase and reducing reactive oxygen species generation, thereby suppressing oxidative stress damage. Additionally, it may improve flap survival through other mechanisms, such as modulating inflammatory responses and suppressing apoptosis. This article systematically reviews the pathological mechanisms and therapeutic advances of skin flap ischemia-reperfusion injury, with a focus on exploring the role of xanthine oxidase inhibitors in flap protection by targeting and regulating oxidative stress pathways, aiming to provide new therapeutic strategies and theoretical basis for clinical prevention and treatment of skin flap ischemia-reperfusion injury.